Review of Insulestremia Jaschhof, 2004 (Diptera; Cecidomyiidae; Lestremiinae) with description of two new species from Brazil - Carmo-Neto, Antonio Marcelino Do; Lamas, Carlos José Einicker; Urso-Guimarães, Maria Virginia (Zootaxa, 2021)
This study presents the first records of the subfamily Lestremiinae and the genus Insulestremia Jaschhof in Brazil. Insulestremia, a previously monotypic genus described from the Galapagos Islands, has three species in Brazil: I. sinclairi Jaschhof, I. amorimi sp. nov. and I. amenti sp. nov. The new species are described, the generic concept is reviewed, and a key to the species of Insulestremia is provided.